2020
DOI: 10.1126/sciadv.abb7781
|View full text |Cite
|
Sign up to set email alerts
|

Trappc9 deficiency in mice impairs learning and memory by causing imbalance of dopamine D1 and D2 neurons

Abstract: Genetic mutations in the gene encoding transport protein particle complex 9 (trappc9), a subunit of TRAPP that acts as a guanine nucleotide exchange factor for rab proteins, cause intellectual disability with brain structural malformations by elusive mechanisms. Here, we report that trappc9-deficient mice exhibit a broad range of behavioral deficits and postnatal delay in growth of the brain. Contrary to volume decline of various brain structures, the striatum of trappc9 null mice was enlarged. An imbalance ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(107 citation statements)
references
References 45 publications
10
50
2
Order By: Relevance
“…Neuroanatomical studies of Trappc9 -/- mice showed overlapping features with Trappc10 -/- mice including reduced brain size predominantly of white matter structures ( S5 Fig ) [ 37 ], although findings of enlarged striatal size were not identified in Trappc10 -/- mice. TRAPPC9 plays a role in the NF-κB signalling pathway through its interaction with NF-κB inducing kinase (NIK) and the beta subunit of IKK, which both regulate the NF-κB pathway [ 11 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroanatomical studies of Trappc9 -/- mice showed overlapping features with Trappc10 -/- mice including reduced brain size predominantly of white matter structures ( S5 Fig ) [ 37 ], although findings of enlarged striatal size were not identified in Trappc10 -/- mice. TRAPPC9 plays a role in the NF-κB signalling pathway through its interaction with NF-κB inducing kinase (NIK) and the beta subunit of IKK, which both regulate the NF-κB pathway [ 11 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRAPPC9 plays a role in the NF-κB signalling pathway through its interaction with NF-κB inducing kinase (NIK) and the beta subunit of IKK, which both regulate the NF-κB pathway [ 11 , 38 ]. Given the associated loss of TRAPPC9 observed with both the TRAPPC10 variants and TRAPPC10 -/- cells, it is plausible that TRAPPC10 loss of function may also impact NF-κB signalling pathways through disruption of TRAPPC9, although the involvement of TRAPPC9 in this pathway in brain has been recently questioned [ 37 ]. Taken together, we define the genetic, clinical and molecular basis of a novel microcephalic neurodevelopmental disorder associated with biallelic TRAPPC10 variants in both humans and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms underlying how the loss of TRAPPC9 impairs brain development and function are yet to be defined, it is that possible these two roles for TRAPPC9 might contribute to neuronal impairment. In this regard, Ke and collaborators (2020) recently reported a Trappc9 knock-out mouse that recapitulated features of human ID [22]. They demonstrated in the mouse model that Trappc9 deficiency impairs learning and memory by causing imbalance of dopamine D1 and D2 neurons [22].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Ke and collaborators (2020) recently reported a Trappc9 knock-out mouse that recapitulated features of human ID [22]. They demonstrated in the mouse model that Trappc9 deficiency impairs learning and memory by causing imbalance of dopamine D1 and D2 neurons [22].…”
Section: Discussionmentioning
confidence: 99%
“…Rab1 and Rab11 are two of the five members of the Rab family that are present in all eukaryotes, and both are essential for the viability of all organisms so far examined (Diekmann et al, 2011;Kloepper et al, 2012). TRAPPII also has some activity on Rab1, although the in vivo significance of this is unresolved (Yamasaki et al, 2009;Thomas & Fromme, 2016;Ke et al, 2020). The TRAPP complexes have also been proposed to have additional roles in various processes including tethering of COPII vesicles, meiotic cytokinesis, ciliogenesis and lipid droplet homeostasis (Cai et al, 2007;Robinett et al, 2009;Westlake et al, 2011;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%